KELAYAKAN PERKEBUNAN KELAPA SAWIT DI PAPUA - djawardi, djawardi (Badan Pengkajian dan Penerapan Teknologi, 2009)
The trading of palm oil in the world from year to year increasing. Along with improvement request of palm oil needed by a adequate palm plantation development. Indonesia as second biggest producer in world also have the importance to extend areal palm plantation. The Extension potency of palm plantation instructed in East Indonesia region. One of big potency is Papua. For development palm plantation in Papua needed a feasibility study. The result of feasibility study an IRR (Internal Rate of Return) of 19.77%; a NPV (Net Present Value) of Rp.180.956.970.000,00; a Profitability Index of 1,11; a BEP (Break Event Point) of 11.499.970 kilograms and Payback Period of 6 year and 2 month. Based on this study, development of Palm plantation is feasible to be implementation in Papua